Divergence of High-Order Harmonic Generation by a Convex Plasma Surface - Chun Yang; Chuliang Zhou; Yinghui Zheng; Dongdong Zhang; Jixing Gao; Yafeng Bai; Rong Qi; Jiayi Qian; Jiayan Gui; Zongxin Zhang; Ye Tian; Zhinan Zeng (Applied Sciences, 2022)
The electron density profile on a plasma surface has a decisive influence on the mechanism and characteristics of the plasma high-order harmonic generation. When the pre-pulse has a similar spatial and temporal distribution as the main laser pulse, the plasma surface on the target will expand to form a convex profile of the similar size as the focal spot of the main pulse. We experimentally observed that the divergence of the harmonics generated by the relativistic laser light incident on a silica target has a saddle-shaped structure. The two-dimensional particle-in-cell simulation with convex plasma surfaces explains the experimental results very well and infers a 0.12<semantics>λL</semantics> plasma scale length around the center of the convex profile. Further, we qualitatively explained that the asymmetry of the saddle-shaped harmonic divergence is caused by oblique incidence.